Carrier’s French and English: "Yoked by Violence Together" - Kamenish, Paula K. (Studies in Canadian Literature, 1992)
Roch Carrier’s La Guerre, Yes Sir! is essentially a novel of decolonization, in which Carrier exposes the dangerously protective values of commitment to the land and the Church and the fallacies of tradition by which French-Canadians have been subordinated and dominated. The novel’s attempt to reject the debilitating view of a peaceful, idyllic, rural life – as portrayed in Louis Hémon’s Maria Chapdelaine – successfully brings to light the violence, both linguistic and behavioural, that characterizes a colonial revolt. Carrier’s characters feel unable to overcome the social, religious, sexual, and economic realities that frustrate them; their struggle unites them as a culturally homologous community, but also ties them to their oppressors, the Anglais.